Gestational Monosodium Glutamate Exposure Effects on Anogenital Distance of Male Rat Pups - Amelya Permata Sari; Cimi Ilmiawati; Mohamad Reza (Faculty of Medicine, Universitas Padjadjaran, 2021)
High-dose Monosodium Glutamate (MSG) expo sure increases the estrogen level in pregnant rats. However, there are limited data available on whether the MSG-related maternal hormonal effects can affect male litters' genitalia phenotype. This study aimed to analyze the impact of MSG on estrogen level in pregnant rats and anogenital distance in male pups. Experiment for this study was performed at the animal facility of Biomedical Laboratory at the Faculty of Medicine, Universitas Andalas, from April 2019 to February 2020. Pregnant Wistar rats were given MSG orally at 2 and 4 mg/g body weight (BW) for 20 days. On day 21, pregnant rats were sacrificed and blood was drawn intracardially. Estradiol serum level was measured by ELISA. Male pups were counted, and the anogenital distance (AGD) was measured. Maternal serum estradiol levels were statistically analyzed by One-Way ANOVA and the AGD of male litters were analyzed by the Kruskal-Wallis test. Results showed that perinatal MSG exposure increased the estradiol level (26.3±4.5 pg/ml; 37.5±6.7 pg/ml; 62.1±8.2 pg/ml in control, 2 mg/g BW, and 4 mg/g BW group, respectively [mean±SD; p=<0.001]) and decreased the AGD (4 mm; 3 mm; 1.5 mm in control, 2 mg/g BW, and 4 mg/gBW group, respectively [median; p=<0.01]) in a dose-dependent manner. Thus, MSG exposure during pregnancy is a risk factor for male rat feminization.